Case report: Atypical case of autoimmune glial fibrillary acidic protein astrocytopathy following COVID-19 vaccination refractory to immunosuppressive treatments - Morishima, Yuto; Hata, Takanori; Nakajima, Sho; Shindo, Kazumasa; Tsuchiya, Mai; Watanabe, Tsubasa; Tahara, Ippei; Kondo, Tetsuo; Kimura, Akio; Shimohata, Takayoshi; Ueno, Yuji (Frontiers in Immunology, 2024)
A 54-year-old Japanese man presented with headache and fever the day after SARS-CoV-2 vaccination. He became deeply unconscious within a week. Brain MRI showed periventricular linear enhancements and a few spotty lesions in the cerebral white matter. Cerebrospinal fluid (CSF) testing showed mild pleocytosis. He was treated with intravenous methylprednisolone and plasma exchange. However, the white matter lesions enlarged to involve the brainstem and cerebellum, and long cord spinal lesions appeared. Anti-glial fibrillary acidic protein (GFAP) antibody was positive in the CSF and serum, and he was therefore diagnosed as autoimmune GFAP-astrocytopathy (GFAP-A). In addition, high-dose immunoglobulin therapy was administered twice, but his symptoms did not improve; the white matter lesions enlarged further, and modified Rankin Scale score increased to 5. A brain biopsy specimen showed infiltration of macrophages and CD4+ lymphocytes together with neuron and oligodendrocytic injuries and glial scar. Although GFAP-A generally responds well to steroids, the present case developed GFAP-A following SARS-CoV-2 vaccination, with refractory to intensive immunosuppressive therapy and atypical pathologic findings of infiltration of CD4+ lymphocytes and demyelination.